Large-earthquake rupturing and slipping behavior along the range-front Maidan fault in the southern Tian Shan, northwestern China. (1st April 2020) - Wu, Chuanyong; Zheng, Wenjun; Zhang, Zhuqi; Jia, Qichao; Yang, Huili
Graphical abstract: Highlights: Trench excavating, terrace surveying and age dating were utilized to study slipping behaviors of a thrust fault. Large-earthquakes on the Maidan fault exhibit a variable-slip behavior. Unbalanced foreland accretionary wedge results in out-of-sequence thrusting for the Maidan fault. The growth of the western Tian Shan orogen was caused by thrust faulting and crustal shortening of block-like pattern. Abstract: Slipping behavior of active thrust faults are not well explored because of their variable vertical displacements governed by dip-angle changes along the fault striking. The range-front Maidan fault (MDF) is a thrust fault in the southern Tian Shan, and exhibits clear paleoearthquake rupturing during the late Quaternary. In this study, based on field investigation, trench exposing, detailed terrace surveying with differential GPS, and optically stimulated luminescence (OSL) dating, we revealed that the latest paleoearthquake on the MDF occurred at ~1.76 ka, and generated a vertical displacement of ~3.0 m. Then, we analyzed the vertical displacements on different terraces of the Yushanguxi River versus the corresponding terrace 10 Be exposure ages. We suggest that the large-earthquake on the MDF is an irregular recurrence. The MDF still has a high seismic risk in spite of only ~1.76 ka elapsed time for the latest paleoearthquake. We propose that the growth and uplift of the western Tian Shan orogen is caused by fault thrusting and crustal shortening of a series of block-like patterns.